2016
DOI: 10.1016/j.rcp.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Validación en Colombia del instrumento para evaluación de la depresión Montgomery-Åsberg Depression Rating Scale (MADRS)

Abstract: Scale (MADRS) en el medio colombiano.Metodología: Estudio de tipo observacional para la validación de una escala. Se precisó la validez de criterio determinando los puntos de corte del instrumento a través de los valores de sensibilidad y especificidad de la gravedad de la enfermedad, al contrastarla con los criterios de la Clasificación Internacional de Enfermedades (CIE-10). Se realizó un análisis factorial de la escala; se determinó la consistencia interna del instrumento; se evaluó la reproducibilidad inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
5
0
3
Order By: Relevance
“…A subsample was newly administered the RCTQ-13 5 days after the first administration to evaluate test-retest reliability. To evaluate construct validity through hypothesis testing, a subsample of 55 people was administered the Young Mania Rating Scale (YMRS) [ 18 ], the Montgomery–Åsberg Depression Rating Scale (MADRS) [ 19 ], the Ruminative Response Scale (RRS) [ 20 ], the Penn State Worry Questionnaire (PSWQ) [ 21 ], and the State-Trait Anxiety Inventory (STAI) [ 22 ]. Discriminant validity was initially approached by comparing the RCTQ-13 scores of the following relevant patient groups: [ 1 ] with hypomanic episodes, [ 2 ] with manic episodes, 3) with manic episodes with mixed features [ 4 ] with depressive episodes, [ 5 ] with depressive episodes with mixed features, and [ 6 ] euthymic patients (in full remission).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsample was newly administered the RCTQ-13 5 days after the first administration to evaluate test-retest reliability. To evaluate construct validity through hypothesis testing, a subsample of 55 people was administered the Young Mania Rating Scale (YMRS) [ 18 ], the Montgomery–Åsberg Depression Rating Scale (MADRS) [ 19 ], the Ruminative Response Scale (RRS) [ 20 ], the Penn State Worry Questionnaire (PSWQ) [ 21 ], and the State-Trait Anxiety Inventory (STAI) [ 22 ]. Discriminant validity was initially approached by comparing the RCTQ-13 scores of the following relevant patient groups: [ 1 ] with hypomanic episodes, [ 2 ] with manic episodes, 3) with manic episodes with mixed features [ 4 ] with depressive episodes, [ 5 ] with depressive episodes with mixed features, and [ 6 ] euthymic patients (in full remission).…”
Section: Methodsmentioning
confidence: 99%
“…Montgomery-Åsberg Depression Rating Scale (MADRS) : hetero-administered questionnaire consisting of 10 statements for major depressive episode diagnosis, which focuses on cognitive, affective, and somatic aspects. It has been validated in Spanish and for Colombia [ 19 ]. Additionally, 7 degrees of severity (0-6) are considered for each item, which associate the even values (0, 2, 4, 6) to statements.…”
Section: Methodsmentioning
confidence: 99%
“…A Brazilian Portuguese version of the SIGMA is not yet available 14,15,21. To the best of our knowledge, the original SIGMA has only been translated to Japanese 18,19,22,23. Given this gap in the literature, we translated and validated the original version of the SIGMA into Brazilian Portuguese, using data from participants enrolled in an ongoing clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results revealed a sensitivity of .81 and specificity of .85 (Paiva-Medeiros et al, 2015). The instrument has been validated in a Colombian sample presenting high internal consistency (α = .92; Cano et al, 2016). In the same study, the findings of inter-rater reliability revealed that the tool was highly reliable (r = .98; Cano et al, 2016).…”
Section: Methodsmentioning
confidence: 67%
“…The instrument has been validated in a Colombian sample presenting high internal consistency (α = .92; Cano et al, 2016). In the same study, the findings of inter-rater reliability revealed that the tool was highly reliable (r = .98; Cano et al, 2016). A meta-analysis by Heo and colleagues (2007), identified that the MADRS and Hamilton Depression Rating Scale (HAM-D) resulted in comparable ratings in assessing changes in overall depressive symptom severity.…”
Section: Methodsmentioning
confidence: 95%